Supplementation of Lauric Acid, Probiotic and their Combination on Performance and Immune Response of Commercial Broiler Chicken - Pappula, Radhika (Indian Journal of Animal Nutrition, 2021)
The objective of the present study was to determine the synergistic effect of lauric acid and probiotic on the performance of broiler chicken. A total of 250-day-old male broiler chicks were randomly distributed into five dietary treatment groups each having ten replicates with five chicks in each and were raised for a period of 42 days. Diets contained T1 - control diet, T2 - 0.05% antibiotic (AB), T3 - 0.05% lauric acid (LA), T4- 0.1% probiotic in the form of Bacillus subtilis PB6 (BS), and T5-0.05% organic acid +0.1% probiotic. The results revealed significantly (P